A pilot study to find the prevalence of diabetes mellitus among newly diagnosed pulmonary tuberculosis and individuals on anti-tuberculosis treatment - S Srinivasa Sarma; Dr. T Jaya Chandra (Tropical Journal of Pathology and Microbiology, 2020)
Introduction: Diabetes Mellitus (DM) is a known risk factor of tuberculosis (TB). Moreover, the risk of getting TB is 3 times more among diabetics compared to the non-diabetics.Materials and methods: Study was conducted in department of Microbiology, GSL Medical College, Rajahmundry. Individuals aged ≥ 18yeras were included in the study. The study participants were divided into two groups. Group A consist of newly diagnosed pulmonary tuberculosis (PT) individuals and individuals on anti tuberculosis treatment (ATT) were included in group B. Two spot sputum samples were collected from the participants, same day sputum collection approach; smear was stained by Ziehl Neelsen staining technique. Blood sample was collected and analyzed by HbA1C technique for sugar estimation.Results: In group A, 17%, 33% and 50% individuals were diagnosed to be normal, prediabetic and diabetic respectively. Whereas this was 7%, 20% and 73% respectively among group B. Age wise, individuals with diabetes were increased in both groups.Conclusion: Diabetes is more among the individuals who are on ATT compared to newly diagnosed PT cases. Studies with large sample size are recommended.